Measuring technological change through an extended structural decomposition analysis: An application to EU-28 primary sectors (2010-2015) - Xesús Pereira López; Małgorzata Anna Węgrzyńska; Napoleón Guillermo Sánchez-Chóez (Economies, 2022)
This paper addresses the input-output structural decomposition for an economic analysis. The objective is to determine the causes of changes in production in these sectors with a particular focus on disaggregating the technological change by distribution factors associated with a specific normalization of the Leontief inverse. In calculating the net multipliers, an attempt was made to exclude each sectors' own consumption in a satisfactory manner. However, the treatment of own consumption when introducing a time factor requires further investigation to avoid questionable measurements. An empirical application is presented regarding agriculture, forestry, and fishing sectors in six EU-28 countries (Austria, Belgium, France, Germany, Italy, and Spain) over the 2010-2015 period. In general, a typical characteristic of primary sectors is the accumulation of a significant amount of their own consumption, facilitated by the design of their own symmetric accounting methods. Therefore, attention is focused on these sectors so as to reveal possible analysis techniques that will provide nuance or validate existing techniques.
Keywords: 330; primary sectors; structural decomposition analysis; technological change